Pollution characteristics, influencing factors and health risks of personal heavy metals exposure: Results from human environmental exposure study in China. (15th July 2022) - Zhao, Xiuge; Li, Zhenglei; Wang, Danlu; Xu, Xiaojing; Tao, Yan; Jiang, Yan; Zhang, Ting; Zhao, Puqiu; Li, Yidu
Abstract: Heavy metals can directly enter the alveolus through respiration and react with proteins and enzymes, leading to various adverse effects on human health. This study aimed to identify the main influencing factors contributing to personal exposure, and the relationships between indoor and outdoor air and personal exposure. A total of 107 paired indoor, outdoor, and personal exposure samples were collected during non-heating and heating periods from urban and rural areas of six typical cities in China. Personal exposure levels of Hg, As, Cd, and Pb during the non-heating period were 0.07, 20.43, 0.53, and 29.97 ng/m 3, and that were 0.08, 28.47, 2.26, and 16.26 ng/m 3 during the heating period, respectively. Personal exposure levels of heavy metals showed temporal, urban-rural, and regional discrepancies. The personal heavy metal exposure was lower than indoors but higher than outdoors, and significantly relative to indoor air for all cities. Heating type and ventilation duration were influence factors of indoor air. Smoking, cooking, heating, and ventilation duration all affected personal exposure of heavy metal. There were non-carcinogenic from personal inhalation of As but the carcinogenic risks of Hg, As, Cd, and Pb were acceptable. Indoor air pollution was the main contributor to personal inhalation health risk. So we should pay more attention to the activity patterns related to indoor air. Highlights: Heavy metal concentrations in indoor/outdoor air and personal exposure were detected. Indoor air did more contribution to personal exposure than outdoor air. Smoking, cooking, and heating influenced personal heavy metal exposure. Compare with outdoor air pollution, indoor air pollution was the main contributor of personal inhalation health risk.